MICRO-MECHANICAL PROPERTIES OF CEMENT AND SLAG COMPOSITES MEASURED BY NANOINDENTATION - Jiří Němeček; Jiří Němeček (Acta Polytechnica CTU Proceedings)
In this study, the micromechanical response of two cementitious composites was characterized by nanoindentation. Pure Portland cement paste and Portland cement with 50 vol. % replaced with granulated blast furnace slag (GBFS) paste were investigated at the age of 28 days. Grid nanoindentation, statistical deconvolution and scanning electron microscopy were used to characterize the main hydration products. Several grids with approximately 500 indents on each sample were performed to obtain modulus of elasticity, hardness and creep indentation parameter. Similar mechanical phases containing calcium silica hydrate, crystalline calcium hydroxide and un-hydrated clinker were found in both samples varying by volume fraction. Blended cement, moreover, contains a phase of slag hydration products with a significantly lower modulus of elasticity. This phase with a high portion of unreacted GBFS is mostly responsible for the difference of mechanical properties of the whole composite.